Effect of clay concentration on the wear behavior and permeability of polypropylene/clay nanocomposites - Horst, María Fernanda (2012)
The permeability and wear behavior of nanocomposites based on polypropylene (PP), polypropylene grafted with maleic anhydride (PPg), and montmorillonite (MMT) have been studied. Clay concentrations of 2-15 wt % and a constant PPg:MMT ratio of 3: 1 were considered. The wear behavior of all materials was studied using the "pin-on-disc" technique. The results indicate that, for given clay concentration, the wear resistance decreases with applied load and that the composites are ∼ 20 times more resistant than their matrices. Moreover, the wear rate of the nanocomposites decreases as the clay concentration increases while that of the corresponding matrices increases. The PP, matrices, and composites display similar values of friction coefficient that neither changes with normal load. Additionally, the oxygen permeability of PP is gradually reduced by the increase of both clay and PPg concentration, being the effect of the filler tactoids much larger than that of the compatibilizer.